THE ROLE OF MICRO-HYDROPOWER PLANTS (MICRO-HPPS) IN SUPPLYING ELECTRICITY TO RURAL AREAS - Tashpulatov Sarvar; Mirzaakhmedov Sayyodjon (Modern American Journals, 2025)
The study explores the potential of micro-hydropower plants (Micro-HPPs) in improving rural electricity supply in Uzbekistan. Using geodetic and GIS analyses, optimal sites within the Fergana region’s irrigation networks were identified. The results show that Micro-HPPs provide an efficient, eco-friendly, and economically viable solution, ensuring stable energy for rural areas and rapid investment returns.
Keywords: Micro-hydropower, Micro-HPPs, Rural electricity supply, Irrigation networks, GIS analysis, Energy efficiency, Renewable energy, Uzbekistan